Pre- and Postsynaptic Dopamine SPECT in Idiopathic Parkinsonian Diseases: A Follow-Up Study. (19th September 2013) - Jakobson Mo, Susanna; Linder, Jan; Forsgren, Lars; Holmberg, Henrik; Larsson, Anne; Riklund, Katrine
Abstract : We prospectively evaluated the diagnostic contribution of 123 I-FP-Cit (DAT) and 123 I-IBZM (IBZM) SPECT in 29 patients with Parkinson's disease (PD) (74.4 ± 4.2 years) and 28 patients with atypical parkinsonian diseases (APD) (74.3 ± 9.2 years). Twelve had multiple system atrophy (MSA) and 16 progressive supranuclear palsy (PSP). Sixteen age-matched healthy controls (HC) were included. DAT and IBZM SPECTs were made at baseline and after 1 year in all PD patients and in 20 (DAT) and 18 (IBZM) of the APD patients, and after 3 years in 22 (DAT) and 17 (IBZM) of the PD patients and in 10 (DAT) and 10 (IBZM) of the APD patients. The relative DAT uptake decrease was faster in PD and PSP than in HC and MSA. In PSP the DAT uptake was lower than in MSA after 1 year but not after 3 years. Baseline IBZM uptake was not significantly different between patients and HC or between PD and APD. One year after initiated dopaminergic treatment the mean IBZM uptake in the MSA patients remained high compared to PSP and after 3 years compared to PD, PSP, and HC. Thus, the pattern of uptake of these ligands over time may be of value in discriminating between these diagnoses.